Linux with operating system concepts - Fox, Richard, 1964- (Boca Raton : Chapman & Hall/CRC, 2014)
A True Textbook for an Introductory Course, System Administration Course, or a Combination Course Linux with Operating System Concepts, Second Edition merges conceptual operating system (OS) and Unix/Linux topics into one cohesive textbook for undergraduate students. The book can be used for a one- or two-semester course on Linux or Unix. It is complete with review sections, problems, definitions, concepts and relevant introductory material, such as binary and Boolean logic, OS kernels and the role of the CPU and memory hierarchy. Details for Introductory and Advanced Users The book covers Linux from both the user and system administrator positions. From a user perspective, it emphasizes command-line interaction. From a system administrator perspective, the text reinforces shell scripting with examples of administration scripts that support the automation of administrator tasks. Thorough Coverage of Concepts and Linux Commands The author incorporates OS concepts not found in most Linux/Unix textbooks, including kernels, file systems, storage devices, virtual memory and process management. He also introduces computer science topics, such as computer networks and TCP/IP, binary numbers and Boolean logic, encryption and the GNU's C compiler. In addition, the text discusses disaster recovery planning, booting and Internet servers. New in this Edition The book has been updated to systemd Linux and the newer services like Cockpit, NetworkManager, firewalld and journald. This edition explores Linux beyond CentOS/Red Hat by adding detail on Debian distributions. Content across most topics has been updated and improved.
OCLC-licensed vendor bibliographic record.
Keywords: Linux; Operating systems (Computers); COMPUTERS / Computer Architecture; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Operating Systems / General